Philosophy in the science classroom: How should biology teachers explain the relationship between science and religion to students? - Woodford, Peter J. (Cult Stud Sci Educ, 2020)
This review explores Thomas Lessl’s “Demarcation as a classroom response to creationism: A critical examination of the National Academy of Science’s Science, Evolution, and Creationism (2008).” Lessl’s work examines philosophical debates about the relationship between science and religion from the perspective of communication dynamics between science teachers and audiences skeptical about evolution. His essay raises a number of important points that might help educators craft statements that are less likely to alienate religious students and to entrench any pre-existing opposition to evolutionary science. However, in this review, I raise a number of criticisms of Lessl’s account of the problems with the approach taken by the National Academy of Science. I argue that many of the criticisms of NAS’s approach to demarcation are not well-supported, and even were they to be strong criticisms, they do not justify skepticism toward evolution or science in general. Ultimately, I argue that addressing Lessl’s concerns means creating space for more intellectually rigorous and satisfying discussions of science and religion, but this is not appropriate in a biology classroom that merely wishes to introduce evolution. Addressing these concerns requires making more space for philosophy in the curriculum.